Heyde Syndrome: An Unusual Cause of Gastrointestinal Bleeding - Dushyant Singh Dahiya MD; Asim Kichloo MD; El-Amir Zain MD; Jagmeet Singh MD; Farah Wani MD; Asad Mehboob DO (SAGE Publishing, 2021)
Heyde syndrome is a multisystem disorder characterized by the classical triad of aortic stenosis, gastrointestinal (GI) angiodysplasias, and acquired von Willebrand syndrome. GI angiodysplasias, common in older patients, are tortuous, thin-walled blood vessels seen in the mucosa or submucosa of the GI tract and are highly prone to rupture resulting in GI bleeds. In this case report, we describe an elderly female with a past medical history of end-stage renal disease and chronic anemia who presented to the emergency department (ED) with complaints of dark-tarry stools and associated abdominal cramping. Patient reported a history of dark-tarry stools and multiple blood transfusions in the past, secondary to severe anemia. An inpatient echocardiogram was performed, revealing severe aortic stenosis. Additionally, gastroenterology was consulted for esophagogastroduodenoscopy and colonoscopy, which were negative for active bleeding. About a year ago, the patient underwent capsule endoscopy at an outlying facility, which was positive for angiodysplasia. Therefore, due to high clinical suspicion, presence of aortic stenosis, and GI angiodysplasia, a platelet function assay was ordered. It was found to be abnormal, pointing to the presence of acquired von Willebrand syndrome. Hence, a diagnosis of Heyde syndrome was established. The patient gradually improved and was discharged with a follow-up appointment with the cardiologist for a possible transcatheter aortic valve replacement procedure. The patient underwent the procedure without complications, after which she did not report episodes of GI bleeding. In this case report, we discuss the presentation, pathophysiology, diagnostic approach, and management of patients with Heyde syndrome.